2018
DOI: 10.1002/admi.201800280
|View full text |Cite
|
Sign up to set email alerts
|

Long Thermal Stability of Inverted Perovskite Photovoltaics Incorporating Fullerene‐Based Diffusion Blocking Layer

Abstract: In this article, the stability of p-i-n perovskite solar cells is studied under accelerated heat lifetime conditions (60 o C ,85 o C and N2 atmosphere). By using a combination of buffer layer engineering, impedance spectroscopy and other characterization techniques, we propose the interaction of the perovskite active layer with the top Al metal electrode through diffusion mechanisms as the major thermal degradation pathway for planar inverted perovskite photovoltaics (PVs) under 85 o C heat conditions. We show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…This specific AZO layer has however already proven its potential as ETL. The exact same commercial reference has been used with success in both organic and perovskite cells, but usually in inverted architectures [57][58][59]. In addition, other low temperature processed AZO materials made by completely different methods [60] have already been used as ETL in normal PSC architecture setups close to the one studied in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…This specific AZO layer has however already proven its potential as ETL. The exact same commercial reference has been used with success in both organic and perovskite cells, but usually in inverted architectures [57][58][59]. In addition, other low temperature processed AZO materials made by completely different methods [60] have already been used as ETL in normal PSC architecture setups close to the one studied in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…We have proposed thick fullerenes diffusion blocking layers to improve the thermal stability of inverted perovskite PVs. 49…”
Section: Resultsmentioning
confidence: 99%
“…In the context of device stability there are several experimental reports highlighting the process of ion migration into the electron/hole blocking layers. 18,19,34 Hence, while most simulation results, today, contain the ''hidden'' assumption that the electron/hole blocking layers also function as ion blocking, we will examine the effect of ion migration into the electron/hole blocking layers. 35 This work was primarily inspired by Rivkin et al 19 who quantified the anion density within the hole blocking layer (HBL) and by Galatopoulos et al 18 which showed that the HBL may function as an ion blocking layer (IBL) too.…”
Section: Introductionmentioning
confidence: 99%